The Role of Physical Activity in the Therapy of Psoriatic Arthritis - Review - Mikołajczak, Karolina (Quality in Sport, 2025)
Psoriatic arthritis (PsA) is a chronic inflammatory joint disease presenting a heterogeneous clinical picture. It is characterized by both skin and joint symptoms, which significantly affects the quality of life of patients. In recent years, there have been rapid developments in the treatment of SD. Modern treatments include the use of classic disease-modifying drugs, as well as biologic drugs and ianus kinase inhibitors. An important component of treatment that is often underestimated is physical activity. Regular exercise has a proven effect on improving joint function, reducing pain and improving overall physical condition in patients with SD. Physical activity can help reduce the severity of disease symptoms, improve joint range of motion, and increase cardiovascular fitness. The purpose of this article is to present modern therapies for SD, taking into account the role of physical activity in the comprehensive treatment of this disease. Both pharmacological and non-pharmacological therapeutic approaches will be discussed.